Handgrip strength assessment at baseline in addition to bone parameters could potentially predict the risk of curve progression in adolescent idiopathic scoliosis - Lau, Rufina Wing Lum; Cheuk, Ka Yee; Hung, Vivian Wing Yin; Yu, Fiona Wai Ping; Tam, Elisa Man Shan; Wong, Lyn Lee Ning; Zhang, Jiajun; Lee, Wayne Yuk Wai; Cheng, Jack Chun Yiu; Lam, Tsz Ping; Lau, Adam Yiu Chung (Frontiers in Pediatrics, 2023)
Adolescent Idiopathic Scoliosis (AIS) shows deranged bone and muscle qualities which are important prognostic factors for curve progression. This retrospective case-control study aimed to investigate whether in addition to the bone parameters, the baseline muscle parameters could predict curve progression in AIS. One hundred and twenty-six female patients with AIS aged 12-14 years old at first clinical visit and had been followed up every 6 months longitudinally (average 4.08 years) until reaching skeletal maturity were included with their records reviewed in the study. They were sub-grouped into progressive and stable groups (increased Cobb angle ≥ or < 6˚ respectively) and evaluated clinical and radiological assessments. Forty-four AIS (34.9%) had an increase of Cobb angle ≥ 6˚ before skeletal maturity.Progressive AIS had lower weight and skeletal maturity, lower trunk (5.7%, p=0.027) and arm lean mass (8.9%, p<0.050), weaker dominant handgrip strength (8.8%, p=0.027), deranged cortical compartment (lower vBMD by 6.5%, p=0.002) and lower bone mechanical properties (stiffness and estimated failure load lowered by 13.2% (p=0.005) and 12.5% (p=0.004)). The best cut-off of maximum dominant handgrip strength is 19.75 kg for distinguishing progressive AIS from stable AIS (75% sensitivity and 52.4% specificity, p=0.011).